How student feedback resulted in marked improvement in examination performance of the pioneer batch of UiTM medical students / Edariah Abu Bakar … [et al.] - Abu Bakar, Edariah; Suleiman, Adlina; Nik Jaafar, Mohd Iskandar; Rajikin, Mohd Hamim; Zainal Abidin, Hakimi; Mansor, Othman; Mohd Nor, Abdul Rahim (Institute of Quality & Knowledge Advancement (InQKA), 2005)
Universiti Teknologi MARA is a young university with lofty ideals to be among the best as a world class institution of higher learning. The Medical Faculty is still an infant, being born recently in June 2003 when the first batch of 20 students began their 5-year medical program at the Jalan Othman Campus in Petaling Jaya. Being pioneers, we had to struggle against all odds, especially in terms of infrastructure and staff shortage. So despite their high CGPA score in the Matriculation examination, students' performance in the First Continuous Assessment was a dismal 65% failure rate. Analysis of the data from their performance in each paper and their feedback identified the problems as: 1) non-conducive learning and examination situations, 2) inadequate time for the essays and practical examinations, 3) unclear labeling of some practical specimens, and 4) inadequate mastery of English. Recommendations were made to address the problems. The interventions instituted resulted in tremendous improvement with 100% pass rate in the Second Continuous Assessment and the First Professional Examination. In the medical program, student feedback, examination performance and question analyses are adopted as routine monitoring and continuing improvement tools in student assessment, on top of the thorough vetting of questions, in line with ISO and international accreditation requirements